Hyperhydration strategies: Are they effective? - Magal, M.; Cohen-Sivan, Y. (Strength and Conditioning Journal, 2005)
The relationship between hypohydration and the increase in heat strain and reduction in exercise performance is well documented. Because of these adverse responses, various researchers have suggested that pre-exercise hyperhydration might be beneficial. Recent research has demonstrated that (a) hyperhydration does not enhance thermoregulation, (b) the only advantage that hyperhydration may provide is the delay of hypohydration, which could account for any performance-related enhancement, and (c) if euhydration is maintained throughout the exercise, hyperhydration (water or glycerol-induced) provides no advantage.